Kognitiv semantikk og nettverksmodellen møter praktisk leksikografi - Berg-Olsen, Sturla; Selvik, Kari-Anne (LexicoNordica, 2015)
The network model of linguistic meaning was developed within the framework of cognitive linguistics as a tool for visualising the semantic structure of polysemous units. The model is based on the notion that linguistic knowledge is grounded in categorisation, and that linguistic units are typically characterised by structured polysemy.We explore the potential usefulness of the network model in the structuring of word senses in a dictionary by transferring two medium-sized entries in the monolingual Norwegian dictionary Norsk Ordbok into semantic networks. Prototypicality and links between senses based on either extension or schematicity are made explicit in the two networks. We argue that the network model is a valuable tool for the dictionary editor faced with the task of identifying word senses and arranging them in a hierarchy.